Recent QFT of Einstein's gravity simplified via ultrahyperfunctions - Plastino, Ángel Luis (2020)
Previously published treatment is rather involved. Here we present a useful approximation to the concomitant derivation that yields a simpler way of handling things and still obtains results quite similar to those yielded by the exact treatment. Our approximation consists of giving the graviton field a simpler, but still quite good approximate form.